CONTEMPORARY LAW AND THE REGULATION OF THE DIGITAL ENVIRONMENT: CHALLENGES OF A NETWORK SOCIETY - Lima Gomes, Alexandre; Christine de Castro Souza Urano, Nadja (Revista Gênero e Interdisciplinaridade, 2023)
The article is a brief study on information technologies and the impacts on society and the science of law, specifically regarding the challenges of international law in the face of international data transfers and regulatory limits